2019
DOI: 10.3390/w11010138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydrological Application of CMADS in Jinhua River Basin, China

Abstract: Evaluating the hydrological application of reanalysis datasets is of practical importance for the design of water resources management and flood controlling facilities in regions with sparse meteorological data. This paper compared a new reanalysis dataset named CMADS with gauge observations and investigated the performance of the hydrological application of CMADS on daily streamflow, evapotranspiration, and soil moisture content simulations. The results show that: CMADS can represent meteorological elements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
2
2
Order By: Relevance
“…The findings of this study are different from those of previous studies, which reported that SWAT model driven by CMADS have a better performance in the research basin (X. Zhou et al, 2019). Base on Fig.…”
Section: Streamflow Simulation Results Of Different Datasetscontrasting
confidence: 99%
“…The findings of this study are different from those of previous studies, which reported that SWAT model driven by CMADS have a better performance in the research basin (X. Zhou et al, 2019). Base on Fig.…”
Section: Streamflow Simulation Results Of Different Datasetscontrasting
confidence: 99%
“…Apparently, using GD (even with sparse coverage) as input to drive SWAT resulted in the best daily streamflow simulation in the YRSR [Figure 6(d)], followed by CFSR [Figure 7(b1)] and CMADS [Figure 7(a1)]. The findings of this study differ from those of previous studies, which reported that the SWAT models driven by CMADS have a better performance in the research basin (Gao et al 2018b;Zhou et al 2019). However, the performance of CMADS and CFSR was poor, with clear underestimation (PBIAS!52.3%) for CMADS and overestimation (PBIAS À18%) for CFSR, especially in the dry season.…”
Section: Effect Of Different Meteorological Datasets As Inputcontrasting
confidence: 69%
“…When establishing the hydrological model, the spatial resolution of the simulation dataset was high, and available CMADS data were thus employed. Compared with the Climatic Research Unit (CRU) data and other widely used datasets, CMADS data have a higher spatial resolution and are more suitably applied in a small watershed [43][44][45][46][47]. For a watershed lacking meteorological data, the CMADS dataset can ensure accuracy on large spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 99%